Organic–inorganic hybrid materials doped with Eu3+, Tb3+, La3+ and lithium Ions - Zelazowska, E.; Rysiakiewicz-Pasek, E.; Borczuch-Laczka, M. (Видавництво Львівської політехніки, 2012)
Organic-inorganic hybrid materials doped with Eu3+, Tb3+ La3+ and lithium ions were produced by sol-gel method using Tetraethyl orthosilicate and poly(methyl methacrylate), ethyl methacrylate, butyl methacrylate, ethyl acetyloacetate as inorganic and organic precursors. Morphology and structure of the hybrids heated at 125°C were characterized by Scanning electron microscopy equipped with Energy dispersive X-ray spectroscopy (SEM/EDS, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), 29Si MAS Nuclear Magnetic Resonance. In all the hybrids, photoluminescence emissions from (5D3), 5D4 → 7FJ and 5D0→ 7FJ transitions of Eu3+ and Tb3+ ions, were revealed.
Keywords: sol-gel; hybrid materials; luminescence; lithium ions; rare-earth doping